Numerical study of skin friction reduction by optimized wall oscillations in a turbulent boundary layer - Chan, Nicholas Keen-Onn. (2011)
In this project, an investigation concerning applying a type of oscillatory wall boundary condition to a turbulent flow to observe its effect on skin friction in the flow is carried out using numerical simulation methods. The type of wall oscillation being introduced to the flow was supposed to have been as close to a square wave as possible without causing numerical difficulties. This report covers some basic concepts related to turbulent boundary flow and explains the methods that were used to carry out the numerical simulation and the related programs used to carry out the analysis of data. Also covered are the related tasks that affect the ability of the simulation to get accurate results. One such problem the presence of Oddball wavenumbers in the calculations may lead to numerical errors in the results, leading to research on correcting the error and the study of the Fast Fourier Transform.